Analisis Alternatif Restruturisasi Utang Atau Penutupan Perusahaan Pada Pandemi Covid-19 Melalui Pkpu, Kepailitan dan Likuidasi - Lilies Anisah; Eni Suarti (Universitas Batanghari Jambi, 2022)
The COVID-19 pandemic situation has caused the destruction of economies throughout the world, including Indonesia. The negligence of the debtor due to the COVID-19 pandemic can be used as a reason to apply for a postponement of debt obligations. Due to the Covid-19 pandemic which disrupts the financial stability of the debtor, so that the debtor cannot pay off his debt or is negligent to the creditor, he can apply for a suspension of debt payment obligations. On the basis of the covid-19 pandemic, that the impossibility of carrying out the contract in the form of financial incapacity. UUK & PKPU provide legal protection to debtors in the midst of the covid-19 pandemic so they don't fall into bankruptcy through PKPU as stipulated in article 222 of the UUK & PKPU. The type of research used is normative legal research. The practice of paying debts through applications for postponement of debt payment obligations (PKPU) based on Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, which starts from the procedure for submitting a PKPU application, temporary PKPU, publication of PKPU decisions, receipt of invoices, making a list of temporary receivables, implementation of the reconciliation meeting for the preparation of a list of permanent receivables, a discussion meeting on the reconciliation plan which includes restructuring of offers to creditors related to the reconciliation plan. The postponement of debt payment obligations (PKPU) is not enough to provide an opportunity for debtors with good intentions to carry on their business. Because the peace process is determined by the creditor, the UUK & PKPU require a reconciliation process with the approval of the creditor. The rules of Article 229 UUK & PKPU give full power to creditors, this causes debtors to depend on the decisions of creditors.